Incidence of Herpes Zoster in a Large Cohort of Persons Living with HIV. (4th October 2017) - Gilbert, Laura; Wang, Xun; Deiss, Robert; Okulicz, Jason; O'Bryan, Thomas; Maves, Ryan; Lalani, Tahaniyat; Schofield, Christina; Ferguson, Tomas; Kronmann, Karl; Whitman, Timothy J; Agan, Brian; et al.
Abstract: Background: Herpes Zoster (HZ) incidence has decreased over 40% in the United States but remains elevated in persons living with HIV (PLWH). HZ vaccine is not routinely recommended for PLWH and provider-prescribing patterns vary greatly. Updated incidence information in this population is needed to guide vaccine strategies. Using data from the US military HIV Natural History Study (NHS), we evaluated the incidence and risk factors for HZ in the modern ART era. Methods: NHS subjects undergo bi-annual visits with laboratory testing, examinations, and records reviewed for clinical diagnosis, including HZ. Analysis was restricted to subjects contributing to follow-up after 2001. Risk factors for HZ (demographic and HIV-specific) were assessed with a multivariate Cox proportional hazards model. Results: Of the 2954 subjects meeting inclusion criteria, 237 (8%) were diagnosed with HZ. At HZ diagnosis, the median age, CD4 count, and viral load were 38.6 years [IQR-30.8, 45.8], 461 cells/uL [IQR-333,  638] and 1900 copies/mL [IQR-50,  19580] respectively. The incidence of HZ was highest prior to 1996 at 3.24 cases/100 person-years (PY) of follow-up (2.96–3.54) and declined significantly over time with 1.9 (1.6–2.3), 1.4 (1.2–1.8), 1.4 (1.1–1.7), and 0.9 (0.7–1.2) cases/100 PY recorded in 1996–2000, 2001–2005, 2006–2010, and 2011–2016, respectively. In the multivariate model, longer time from HIV diagnosis to ART initiation was associated with HZ. ART use, higher CD4 count, recent year of HIV diagnosis, and older age were protective (Table 1). Conclusion: HZ remains a common diagnosis in the ART era. NHS subjects with HZ were in the fourth and fifth decades of their life and had preserved CD4 counts highlighting the need for HZ vaccine safety and efficacy studies to help guide provider practice. Delays in ART initiation were associated with HZ emphasizing the need for compliance with current ART guidelines. Disclosures: All authors: No reported disclosures.